Hukum Tiga Tahap Perkembangan Intelektual Auguste Comte Dalam Perspektif Filsafat Pendidikan Dan Relevansinya Terhadap Pendidikan Agama Islam - Dedy Rizaldi; Syamsul Rijal; Firdaus M. Yunus; Silahuddin (Kalam: Jurnal Agama dan Sosial Humaniora, 2026)
This study aims to analyze the theory of the Law of Three Stages of intellectual development proposed by Auguste Comte namely the theological, metaphysical, and positive stages from the perspective of the philosophy of education, as well as its relevance to the development of Islamic Religious Education (PAI). The research employs a qualitative method with a library research approach. Data analysis techniques include content analysis and philosophical analysis of primary and secondary sources to produce a comprehensive understanding of the integration between scientific rationality and the spiritual dimension. The results of the study indicate that although Comte’s positivism contributes significantly to scientific methodology and the use of rationality and empiricism in modern education, this paradigm tends to reduce the spiritual and moral dimensions by viewing the theological stage as a phase that must be abandoned. In contrast, the perspective of Islamic education offers an integrative epistemology, in which knowledge is derived simultaneously from revelation, reason, and empirical experience.